2005
DOI: 10.1111/j.1365-2036.2005.02528.x
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole delays gastric emptying in healthy volunteers: an effect prevented by tegaserod

Abstract: SUMMARYBackground: Proton-pump inhibitors effectively suppress stomach acidity. They are widely used for treating gastro-oesophageal reflux disease and related conditions. While generally safe, omeprazole and other proton-pump inhibitors can delay gastric emptying. Aim: To test the hypothesis that tegaserod can normalize or prevent omeprazole-induced delay in gastric emptying.Methods: This was a randomized, double-blind, placebocontrolled, parallel group study in 40 healthy male volunteers. After informed cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
44
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 23 publications
2
44
0
3
Order By: Relevance
“…This inhibition of gastric emptying caused by rabeprazole is consistent with some previous studies using PPI (Benini et al 1996;Rasmussen et al 1997Rasmussen et al , 1999Parkman et al 1998;Anjiki et al 2005;Tougas et al 2005;Takahashi et al 2006), but at variance with others that failed to show any association between PPI administration and gastric emptying (Vidon et al 1993;Jones et al 2003;Grudell et al 2006). It has been supposed that such discrepancies may be partly explained by the use of different meal compositions and forms, and by the different methods for evaluating gastric emptying.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This inhibition of gastric emptying caused by rabeprazole is consistent with some previous studies using PPI (Benini et al 1996;Rasmussen et al 1997Rasmussen et al , 1999Parkman et al 1998;Anjiki et al 2005;Tougas et al 2005;Takahashi et al 2006), but at variance with others that failed to show any association between PPI administration and gastric emptying (Vidon et al 1993;Jones et al 2003;Grudell et al 2006). It has been supposed that such discrepancies may be partly explained by the use of different meal compositions and forms, and by the different methods for evaluating gastric emptying.…”
Section: Discussionsupporting
confidence: 87%
“…Although there have been conflicting reports on PPI and gastric emptying, significant studies reported delayed gastric emptying by PPI administration (Benini et al 1996;Rasmussen et al 1997Rasmussen et al , 1999Parkman et al 1998;Anjiki et al 2005;Tougas et al 2005;Takahashi et al 2006), while other studies failed to show any significant change in the gastric emptying by the treatment (Vidon et al 1993;Jones et al 2003;Grudell et al 2006). Since a sufficient amount of gastric acid is essential for the generation of luminal NO in the stomach originating from dietary nitrate (McKnight et al 1997;Iijima et al 2003), the effect of dietary nitrate on gastric emptying, if any, would be modified by co-administration of PPI.…”
mentioning
confidence: 99%
“…This observation highlights the unresolved question of whether the low-fat, EggBeaters meal is even the optimal solid meal substrate; indeed, significantly different emptying between the EggBeaters meal and a radiolabeled liver at 3 h was reported in the original report ''validating'' the EggBeaters meal [1]. GES also has utility in the evaluation of the motility effects of drugs, such as has been reported for studies utilizing the 2 % fat EggBeaters meal [7,8] and with the higher-calorie (296 kcal) and 32 % fat scrambled eggs meal [9,10].…”
mentioning
confidence: 75%
“…In contrast, the option of long-term PPI therapy was associated with a significant body weight gain in the present study. Omeprazole and other PPIs delay gastric emptying [6][7][8][9] , which induces postprandial fullness, dyspeptic symptoms, gastrointestinal bacterial overgrowth, and subsequent weight loss [10,11] . Our results have clearly demonstrated that long-term PPI therapy contributed significantly to body weight changes in patients with GERD by relieving the adverse symptoms rather than altering the state of gastric emptying.…”
Section: Discussionmentioning
confidence: 99%